Applied Anatomical Insights Of Asthi And Sandhi From Sushruta Samhita: A Review With Clinical Correlations - Singh, Ramanuj Kumar; K. Tokare , Rajshekhar; Tiwari , Parmod Anand (Journal of Neonatal Surgery, 2025)
Anatomy forms the foundational basis of medical science, both in modern and traditional systems like Ayurveda. The Sushruta Samhita, a classical text of Ayurveda, is acclaimed for its comprehensive exploration of human anatomy and surgical principles. Among its various contributions, the descriptions of Asthi (bones) and Sandhi (joints) stand out for their clarity and clinical applicability. This review article aims to revisit and critically analyze the concepts of Asthi and Sandhi as delineated in the Sushruta Samhita, comparing them with contemporary anatomical understanding, and highlighting their relevance in Ayurvedic clinical practice.Sushruta classified bones based on structure and function into five types and detailed 360 bones in the human body, including teeth, nails, and hair roots, which differ from modern counts. Sandhis were categorized into movable and immovable types, resembling synovial and fibrous joints in modern science. The text also connects Asthi and Sandhi with Dhatu Poshana (tissue nourishment), Marma (vital points), and various disease processes.This review evaluates the applied aspects of these structures in clinical contexts such as fracture (Bhagna) management, joint disorders (Sandhigata Vata), and Panchakarma therapies like Basti and Abhyanga. The timeless insights of Sushruta offer valuable perspectives for modern orthopedics and integrative approaches. Emphasizing these classical anatomical concepts fosters a better understanding of musculoskeletal health, enhancing diagnostic and therapeutic outcomes in Ayurveda. The review concludes that revisiting these traditional anatomical frameworks can inform and enrich contemporary medical and surgical practices.